La Péri-Pneumonie Contagieuse Bovine (PPCB) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Une maladie qui demeure difficile à diagnostiquer.